As técnicas de enxertia no município de Abaetetuba-PA - RIBEIRO, Maria José Pereira (2024)
Asexual reproduction in plants can occur by vegetative propagation through stems, leaves or roots.The mechanisms of development of new plants can occur spontaneously in nature or can be manmade, mainly for economic cultivation of certain plants.Grafting is a method of obtaining new plants by asexual process of vegetative propagation, with human intervention.Grafting is the union of the plant tissue, usually of different species, starting to form a plant with two parts: the graft (fork) and rootstock (horse).The fork, rider or graft is the top, which will produce the fruits of cultivar desired.And the horse or rootstock is the bottom, which will form the root system, which is to support the basic functions of the plant, supply of water and nutrients and plant adaptation to soil conditions, climate and diseases.This technique is only possible because plant cells are totipotent.The secondary meristems initiate a large production of new cells through successive mitoses, which subsequently undergo cell differentiation for the formation of new tissue, causing thus the union (welding) of parts of the grafted tissue.The grafting can be performed by several methods, the most common being to grafting, the grafting and budding and its variations.This technique has several advantages, such as, for example, the joining of various desirable traits in a single plant, the plant need not pass for a period of youthfulness to go into production, the formation of smaller plants and ensuring genetic material.